Kesenjangan Digital Antarsiswa di Era Ekonomi Atensi; Studi Kasus di Madrasah Aliyah Al-Ibrohimy Galis - Arifin, Moh. Samsul; Fauzi, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2024)
In the context of the attention economy era, where human attention has become a valuable commodity, this research explores digital disparities with a focus on a case study at Madrasah Aliyah Al-Ibrohimy Galis. Digital disparities are identified through signs emerging among students, particularly concerning economic factors, digital literacy, and regulations on the use of communication technology within the Islamic boarding school environment. This study utilizes the attention economy framework as a theoretical foundation, illustrating intense competition to capture students' attention in the digital environment. The research methodology involves student surveys, interviews, and document analysis. The success of this study provides insights into strategies to reduce the digital gap in Madrasah Aliyah Al-Ibrohimy Galis. The research reveals the existence of inter-student digital disparities at MA Al-Ibrohimy, influenced by variations in digital literacy, economic disparities, and regulations governing information technology usage in the boarding school environment. The conclusion emphasizes the need for special attention to students' digital literacy levels, addressing economic disparities, and reviewing technology usage regulations in the boarding school. Recommendations are provided to local management and stakeholders to enhance access and utilization of information technology at MA Al-Ibrohimy, thereby reducing the digital gap and supporting equality in learning. This research underscores the urgency of addressing digital disparities in the Islamic education setting, considering the increasing role of technology in the dominant attention economy.